O véu não cobre pensamento: imigrantes muçulmanas em São Paulo - Zaia, Marcia Cristina (2006)
The purpose of the present work is to discuss the relations between religion and immigration, from an intercultural perspective, through the life history of immigrant Muslim women in the city of São Paulo, Brazil, during their acculturation process. In this work, this concept is based upon Intercultural Psychology formulations, as the necessary result of a contact between two cultures, which can lead to the adoption of integration or separation strategies. Through the study of a minority that has been scarcely investigated in Brazil, this work indicates the relevancy that religion can acquire in a migratory context, since it is one of the constituent elements of the ethnic identity